Imaging Constitutive Exocytosis with Total Internal Reflection Fluorescence Microscopy - Schmoranzer, Jan (The Rockefeller University Press, 2000)
Total internal reflection fluorescence microscopy has been applied to image the final stage of constitutive exocytosis, which is the fusion of single post-Golgi carriers with the plasma membrane. The use of a membrane protein tagged with green fluorescent protein allowed the kinetics of fusion to be followed with a time resolution of 30 frames/s. Quantitative analysis allowed carriers undergoing fusion to be easily distinguished from carriers moving perpendicularly to the plasma membrane. The flattening of the carriers into the plasma membrane is seen as a simultaneous rise in the total, peak, and width of the fluorescence intensity. The duration of this flattening process depends on the size of the carriers, distinguishing small spherical from large tubular carriers. The spread of the membrane protein into the plasma membrane upon fusion is diffusive. Mapping many fusion sites of a single cell reveals that there are no preferred sites for constitutive exocytosis in this system.